Uncovering the Role of RNA-Binding Proteins in Gene Expression in the Immune System - Díaz-Muñoz, Manuel D.; Turner, Martin (Frontiers in Immunology, 2018)
Fighting external pathogens requires an ever-changing immune system that relies on tight regulation of gene expression. Transcriptional control is the first step to build efficient responses while preventing immunodeficiencies and autoimmunity. Post-transcriptional regulation of RNA editing, location, stability and translation are the other key steps for final gene expression and they are all controlled by RNA binding proteins. Nowadays we have a deep understanding of how transcription factors control the immune system but recent evidences suggest that post-transcriptional regulation by RNA binding proteins is equally important for both development and activation of immune responses. Here we review current knowledge about how post-transcriptional control by RNA binding proteins shapes our immune system and we discuss the perspective of RNA binding proteins being the key players of a hidden immune cell epitranscriptome.